First record of the genus Pion Schiødte, 1839 (Hymenoptera: Ichneumonidae: Ctenopelmatinae), from Japan, with description of a new species - Watanabe, Kyohei (Zootaxa, 2016)
The genus Pion Schiødte, 1839, is newly recorded from Japan based on a new species, P. japonicum sp. nov. This species closely resembles the Chinese species P. qinyuanensis Chen, Sheng & Mao, 1998, but it can be distinguished from the following combination of character states (male of P. qinyuanensis is unknown): lateromedian longitudinal carina of propodeum completely parallel, not convergent anteriorly (almost parallel but slightly convergent anteriorly in P. qinyuanensis); malar space 0.6 times as long as basal width of mandible (0.5 times in P. qinyuanensis); antenna with 28–29 flagellomeres (30–34 in P. qinyuanensis); hind femur black, rarely tinged with red (largely red in P. qinyuanensis); and hind tibia yellowish-brown basally, black apically (entirely black in P. qinyuanensis). A key to world species of Pion is also provided.